Elastic-plastic fracture mechanics investigation on two interacting cracks - Tan, Kok Keong (2017)
There are many kinds of defects and fractures which can be found in the material. To study these fractures and defects, one of the most common and suitable parameters used is the stress intensity factor. The stress intensity factor states the stress condition at a crack tip, with respect to the rate of crack development and is often implemented to ascertain failure benchmark because of fracture [1]. One way of studying the stresses in these defects is by a numerical investigation system known as the finite element method. This method is widely used to solve engineering problems due to its flexibility and multiplicity as an analysis tool. This report begins the theoretical part of stress intensity factor and finite element method. On top of these, there will also be two different cases of crack analysis being reviewed. Firstly, the study of two interacting cracks on an infinite plate which are perpendicular to its load. Secondly, two interacting cracks, with one inclined at an angle will be analysed, with the stress intensity factors assessed. To obtain these test results, a detailed procedure from a software using finite element method known as Abaqus CAE (Computer Aided Engineering) will be performed. This is an application which can be used for envisaging and assemblies of the finite element investigation outcome as well as modelling and testing of mechanical components. Lastly, theoretical results will be normalised with the results obtained from the software and conclusion will be made in the later part of the report.